Transforming the passenger journey: The role of artificial intelligence in future-ready airports - Piedade, Lúcia; Marques, Mariana; O’Neill, Alexandra; Macau, Ana (International Journal of Innovative Research and Scientific Studies, 2025)
Air transport is undergoing a profound digital transformation, with artificial intelligence (AI) emerging as a key enabler of efficiency, security, personalization, and sustainability. This study investigates how AI is reshaping airport operations and passenger journeys, combining an extensive literature review with original quantitative research involving 744 air travelers. The research employs a descriptive and exploratory design to assess public perceptions of AI integration across areas such as automated check-ins, facial recognition, predictive analytics, and sustainability management. Statistical and thematic analyses reveal high acceptance of AI for safety, logistics, and environmental optimization, yet persistent concerns about privacy, transparency, and ethical governance. Results show that while 95% of respondents trust AI in security contexts and 85% value its potential for personalization, 87% prioritize sustainability as the key criterion for future airport innovation. The findings highlight a nuanced balance between technological enthusiasm and ethical caution. The study concludes that AI must be implemented through human-centered, transparent, and sustainability-aligned frameworks to gain public trust and long-term legitimacy. Ultimately, AI is positioned not merely as a technological upgrade but as a strategic instrument for building inclusive, resilient, and future-ready airports.